If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -17 = 8y + -41 Reorder the terms: -17 + 2y = 8y + -41 Reorder the terms: -17 + 2y = -41 + 8y Solving -17 + 2y = -41 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. -17 + 2y + -8y = -41 + 8y + -8y Combine like terms: 2y + -8y = -6y -17 + -6y = -41 + 8y + -8y Combine like terms: 8y + -8y = 0 -17 + -6y = -41 + 0 -17 + -6y = -41 Add '17' to each side of the equation. -17 + 17 + -6y = -41 + 17 Combine like terms: -17 + 17 = 0 0 + -6y = -41 + 17 -6y = -41 + 17 Combine like terms: -41 + 17 = -24 -6y = -24 Divide each side by '-6'. y = 4 Simplifying y = 4
| 4.85-6.4+1.11=22.6 | | 2.03x-1=4 | | 6*3.14*(0.000899)*0.5(x)-0.00005223399=0 | | (3x-1)(4x+9)= | | -3y+2x=9 | | 3x-1*4x+9= | | 5t+6+3(t+2)=5t+3t+6+6 | | 1+6x+6=-11 | | -8y+(-7x+3y-2)= | | -8(2+7n)=-6n+343 | | 0.5m+0.25+0.75m=12 | | 4(2x-4)-3(7x+2)=0 | | Y-1=1/3(x-4) | | 0.3(2x-4)=-0.5(x-8) | | W=n+xy | | 11c^2+13c= | | 4x+5x=3x-4 | | -3(x+3)=9 | | x/4?10=15 | | 10?9x=82 | | 5t+6+3(t+2)=5t+6+3t+6 | | 4+5x+3x-4= | | 2=-2p+3p | | -5(15+12n)=47-60n | | 5x+4=2x-17 | | 81/4-52/3= | | 81/4-5/23= | | 7=8y-3 | | 6t-4=2[(2+1)+2] | | 8x-5y=29 | | 5/6f-10=60 | | 5X+50=3x+340 |